Dzikir sebagai Mekanisme Coping dalam Menurunkan Stres dan Kecemasan pada Mahasiswa: Kajian Literatur - Nurhasanah Putri; Laila Azmi; Salman Ruhul Jadid; Rahmadianti Aulia (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Stres and anxiety are common psychological problems experienced by university students and have been shown to negatively affect academic performance and psychological well-being. Dhikr, as an Islamic spiritual practice, is increasingly being studied as a potential coping mechanism to help students manage academic pressures. However, existing studies remain fragmented across different psychological outcomes, intervention forms, and methodological approaches. This study aimed to synthesize empirical findings regarding the role of dhikr as a coping mechanism in reducing stress and anxiety among university students. A Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted using four databases, namely Scopus, PubMed, Google Scholar, and Garuda, covering publications from 2016 to 2026. Following predefined inclusion and exclusion criteria, 12 articles were included for final analysis. The findings indicate that dhikr has the potential to reduce anxiety and stress across various contexts and may support the development of more adaptive coping mechanisms through emotional regulation, psychological tranquility, and improved self-control. Nevertheless, the findings should be interpreted with caution due to methodological limitations in the included studies, such as small sample sizes, the absence of control groups, and inconsistencies across some of the included findings. This review provides a more comprehensive understanding of the role of dhikr in supporting students' psychological well-being and highlights the need for future studies employing more rigorous research designs and more diverse student populations.